Nervenkompressionssyndrome des Nervus medianus und Nervus radialis am Ellbogen: CME : zertifizierte Fortbildung - Cavalcanti Kußmaul, Adrian; Hermann, Wieland; Boever, Julie; Ayache, Ali; Unglaub, Frank (Die Orthopädie, 2025)
Nerve compression syndromes of the median and radial nerves at the elbow are usually caused by a combination of traction and pressure and are mainly characterized by loss of strength and dull, localized elbow pain. Muscular functional impairments can occur, whereas sensory impairments are less common. The diagnostics including a detailed medical history, neurological examination with, for example, lateral comparison muscle testing and imaging procedures such as X‑ray, sonography or magnetic resonance imaging (MRI) are essential. In the early stages, conservative treatment with immobilization and infiltrative cortisone treatment can be successful. If symptoms persist or progress, surgical interventions using magnifying glasses (from 2.5×) and microsurgical instruments or a microscope are indicated. It is particularly important to protect the vascular supply and the nerve gliding tissue in order to ensure optimal regeneration and thus function. With timely diagnostics and treatment the prognosis is good.
Online publiziert: 7. März 2025
Gesehen am 12.06.2025